Optimizing Religious Moderation Awareness Through Public Relations Campaign Approach - Khoiriyah, Khoiriyah (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2023)
Religious moderation in the student environment is an urgent need because there are still a number of students who show intolerant behavior. Findings from research conducted by the Center for Islamic and Community Studies (PPIM) at the State Islamic University (UIN) Jakarta show that around 30.16 percent of students in Indonesia show intolerant attitudes. Sirojudin, a researcher from PPIM, stated that around one in three students shows symptoms of intolerance(Purnamasari, 2021). Likewise, approaching the 2024 Political Year, it is important to have social media etiquette, with the aim of preventing extreme polarization due to differences in opinion and political preferences becoming increasingly important.The threat of polarization is increasing due to hoax content, disinformation and even slander that can be spread by netizens without accountability. The public is reminded to avoid black campaigns and not spread false information both in the real world and in cyberspace, because this can divide society and threaten harmony among citizens. This article focuses on religious moderation using a Public Relations approach by making students as agents of change. Millennials are more appropriate for campaigning because it suits their group and makes use of social media. Apart from that, students act as Social Control who act as intermediaries between the government and society. The focus of this research is at the Probolinggo Muhammadiyah Islamic High School as a multicultural campus, the majority of students are NU with the aim of inviting the academic community and students to have a moderate attitude. The paradigm used in this research is post-positivistic. Qualitative approach with field research type with case study method. The purpose of this research is to evaluate the success of the Public Relations campaign planning stages carried out by students in supporting the religious moderation campaign and whether the campaign is effective in forming attitudes of religious moderation.